Wooden Chest Syndrome: A Case Report of Fentanyl-Induced Chest Wall Rigidity - Nathaniel R. Rosal DO; Franklin L. Thelmo DO; Stephanie Tzarnas MD; Lauren DiCalvo DO; Shafaq Tariq MD; Craig Grossman MD (SAGE Publishing, 2021)
Wooden chest syndrome (WCS) describes a finding of fentanyl-induced skeletal muscle rigidity causing ventilatory failure. Known primarily to anesthesiology, pulmonary, and critical care fields, WCS is a rare complication that may affect patients of all ages if exposed to intravenous fentanyl, characterized by a patient's inability to properly ventilate. Given the rise of synthetic opioid deaths across the United States in the past decade, an understanding of all of fentanyl's effects on the body is necessary. In this article, we present a case of WCS in a patient with acute respiratory distress syndrome in a 61-year-old female.